Neuroprotective Potential of Tinospora cordifolia in Attenuating Hippocampal CA3 Neuronal Damage in Pregnant Wistar Rats and their Neonates Exposed to Prenatal Vibration Stress and Maternal Separation - Rao KG, Mohandas; LS, Ashwini; S Rai, Kiranmai; Shetty, Somashekar; Rao, Guruprasad; Udupa, Padmanabha; Suryavanshi, Chinmay Ajit (Jordan Journal of Pharmaceutical Sciences, 2025)
Background: Prenatal stress detrimentally impacts cognition, behavior, and psychosocial traits. Tinospora cordifolia (TC) is known for its antistress and cognitive enhancement properties. However, its effectiveness against stress induced by maternal separation and vibration is not well-documented. The purpose of the study was to assess the neuroprotective effects of TC on neonatal rats who have experienced the prenatal vibration stress and also stress caused by maternal separation. Methods: Pregnant Wistar rats in the stressed group experienced three hours of daily vibration stress from 7-16 days of gestation. The treatment group was given 6 mg/kg of TC extract before vibration stress. The neonates were separated from their mother and treated with TC postnatally. At the end treatment period, the rats were subjected to spatial learning task. Following this, animal brains were processed for Golgi cox staining to study the CA3 neuronal arborization. Results and conclusion: TC-treated mothers showed significantly better spatial learning than those subjected to vibration stress alone. Neonates exposed to prenatal stress took longer time to find the target quadrant, indicating impaired spatial memory, which improved with TC treatment. Increased dendritic branching in CA3 neurons was observed in both TC-treated mothers and neonates. TC extract improves the spatial learning in rats by attenuating the hippocampal CA3 neural damage induced by prenatal vibration stress and maternal separation.